2010
DOI: 10.1177/154193121005402720
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Team Training: Effective Feedback

Abstract: Mission success in military operations is determined by team actions and is dependent on effective team training. Training has the potential to strengthen or weaken a team, and feedback during training is cited as a cornerstone for effective training. The Army currently employs an after-action review (AAR) process to provide post-action feedback to teams. Traditional AAR dynamics, with teammates and a facilitator in the same room, are being disrupted by the growing frequency of geographically-distributed teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the effectiveness of including feedback with debriefs (Oden, 2009). In a study that compared the impact of debriefing only and audio-visual feedback plus debriefing, Dine, Gersh, Leary, Riegel, Bellini, and Abela (2008) found that performance outcomes on a CPR task did change, whereby there were significant improvements in performance when debriefing was combined with feedback.…”
Section: Identifying Impact: Current State Of the Science Within Tdismentioning
confidence: 99%
“…Several studies have investigated the effectiveness of including feedback with debriefs (Oden, 2009). In a study that compared the impact of debriefing only and audio-visual feedback plus debriefing, Dine, Gersh, Leary, Riegel, Bellini, and Abela (2008) found that performance outcomes on a CPR task did change, whereby there were significant improvements in performance when debriefing was combined with feedback.…”
Section: Identifying Impact: Current State Of the Science Within Tdismentioning
confidence: 99%
“…For each of the three training missions (Mission 1, Mission 2, and Mission 3), the participant was required to search a different set of buildings while following procedures outlined in the learning objectives (LOs), which were loosely adapted from prior research using the same virtual environment to train teams (Oden, 2008). The LOs included procedures for: (1) entering and exiting buildings, (2) clearing buildings, and (3) communicating with Headquarters (played by a confederate).…”
Section: Simulated Missionsmentioning
confidence: 99%